Patterns of hypometabolism in frontal lobe epilepsy originating in different frontal regions. Issue 9 (14th July 2022) - Zhao, Zexian; Li, Hong; Wang, Shan; Chen, Cong; He, Chenmin; Hu, Lingli; Zheng, Zhe; Zhu, Junming; Ding, Meiping; Wang, Shuang; Ding, Yao
Abstract: Objectives: Analysis of FDG‐PET imaging commonly shows that hypometabolism extends into extra‐epileptogenic zones (extra‐EZ). This study investigates the distribution patterns of hypometabolism in frontal lobe epilepsy (FLE) originating in different frontal regions. Methods: Sixty‐four patients with FLE were grouped by EZ localization according to Brodmann areas (BAs): Group 1 (the frontal motor and premotor area), BAs 4, 6, and 8; Group 2 (the inferior frontal gyrus and opercular area), BAs 44, 45, and 47; Group 3 (the dorsal prefrontal area), BAs 9, 10, 11, and 46; and Group 4 (the medial frontal and anterior cingulate gyrus), BAs 32 and 24. Regions of extra‐EZ hypometabolism were statistically analyzed between FLE groups and healthy controls. Correlation analysis was performed to identify relationships between the intensity of hypometabolism and clinical characteristics. Results: Significant hypometabolism in the ipsilateral (Groups 1 and 4) or bilateral (Groups 2 and 3) anterior insulae was found. Groups 1 and 4 presented with limited distribution of extra‐EZ hypometabolism, whereas Groups 2 and 3 showed widely distributed extra‐EZ hypometabolism in the rectus gyrus, cingulate gyrus, and other regions. Additionally, the intensity of hypometabolism was correlated with epilepsy duration in Groups 2 and 3. Conclusions: All FLE groups showed hypometabolism in the anterior insula. In addition, distinct patterns of extra‐EZ hypometabolism were identified for each FLE group. This quantitative FDG‐PET analysis expanded our understanding of the topography of epileptic networks and can guide EZ localization in the future.